2020
DOI: 10.32479/ijeep.10590
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Co2 Emissions Through Biogas, Wind and Solar Energy Production: Evidence From Indonesia

Abstract: CO 2 emission has become a growing concern for most of the countries and many factors or reasons have been found to enhance this emission in one way or the other. In this particular study, the impact of biogas energy, wind energy and solar energy production is supposed to be studied on CO 2 emission in Indonesia. The author has collected data for research purpose from Indonesia. The data covers the period of 29 years and has been collected from authentic databases. After data collection process, several tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our study is in line with the previous studies. Yuaningsih et al (2020) analyzed the impact of various sources of renewable resources, including solar energy, on environmental quality and concluded that solar energy is a significant channel to reduce environmental degradation in Indonesia. Sharif et al (2021) also did the same analysis and proved that solar energy plays an essential role in decreasing environmental degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is in line with the previous studies. Yuaningsih et al (2020) analyzed the impact of various sources of renewable resources, including solar energy, on environmental quality and concluded that solar energy is a significant channel to reduce environmental degradation in Indonesia. Sharif et al (2021) also did the same analysis and proved that solar energy plays an essential role in decreasing environmental degradation.…”
Section: Resultsmentioning
confidence: 99%
“…According to the empirical findings, RE use is negatively associated with CE in the selected panel. Further, Yuaningsih et al (2020) explained the role of different sources of RE (biogas, wind, and solar) in reducing CE for the Indonesian economy. According to the study, different sources of RE, especially solar and wind, help to decrease CE.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation